PROFIL PCR-RFLP LOKUS omp2b ISOLAT Brucella abortus ASAL TERNAK RUMINANSIA BESAR BEBERAPA DAERAH DI INDONESIA - , DRH. MARIO LINTANG PRATAMA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The approach of the polymerase chain reaction â restriction fragment length polymorphorisms (PCR â RFLP) was used to characterize four isolate from different geographic origins and hosts representing B. abortus bv. 1 of Indonesian strain. Four B. abortus bv. 1 isolates were randomly selected from old and new collection of brucellosis cases which were isolated from submitted samples at the Veterinary Research Institute (BBALITVET) and Disease Investigation Center (DIC) Maros. The sample originated from Kupang â West Timor, Jakarta, Bandung â West Java and Maros â South Sulawesi. Analysis of PCR products of the locus omp2b digested with two restriction enzymes, i.e. AluI and PstI revealed two variables, such as the sum of fragment and variation at molecular mass within fragment of omp2b. The result showed that the amplified product was separated into two fragment with different molecular mass. Restriction enzyme, i.e. AluI and PstI digests of a 1236 bp segment amplified from locus omp2b of indonesian strain B. abortus showed distinctive profile. Analysis of the AluI site polymorphisms in the B. abortus omp2b gene enabled host specific identification. In B. abortus isolates from Jakarta and Bandung â West Java a two fragment was observed : 760 bp and 371 bp. The lower 12 bp and 93 bp band is too small to be visualized on gel electrophoresis. In contrast, B. abortus isolates from Maros â South Sulawesi and Kupang â West Timor showed two different fragment : 755 bp and 366 bp. The PstI site polymorphisms in the B. abortus omp2b gene enabled specimen origins identification. The restriction pattern of PstI site for three isolates, such as Jakarta, Maros â South Sulawesi and Kupang â West Timor showed similar molecular mass at 875 bp and 273 bp. The lower 88 bp band is too small to be visualized on gel electrophoresis. In contrast, B. abortus isolates from Bandung â West Java showed two different fragment : 885 bp and 283 bp. The result informs understanding of the use PCR â RFLP can not confirm geographics origin status, but confirm host specific and specimen origins identification.